Development, Feasibility, and Acceptability of a Brief, Adjunctive Cognitive-Behavioral Intervention Aimed at Encouraging Rapid Response to Intensive Eating Disorder Treatment. Issue 1 (February 2021) - MacDonald, Danielle E.; McFarlane, Traci; Dionne, Michelle M.; Trottier, Kathryn; Olmsted, Marion P.
Abstract: This study reports on feasibility and acceptability outcomes of a brief, adjunctive cognitive-behavior therapy (CBT) intervention focused on encouraging rapid behavior change in intensive eating disorder treatment (CBT-RR). Effectiveness outcomes of this study have been previously reported (MacDonald et al., 2017). CBT-RR was found to be feasible to implement and acceptable to patients, relative to the comparison condition (motivational interviewing [MI]). Rates of treatment retention were good in both conditions. CBT-RR participants reported higher goal-related alliance with the therapist compared to MI, whereas task-related and bond-related alliances with the therapist were similar between interventions. Both groups reported high levels of homework completion, and strong satisfaction with treatment. Following demonstration of feasibility and acceptability, the second part of this paper provides a detailed description of how we conceptualized and developed the CBT-RR intervention. A detailed description of the protocol components and session content is provided, with a fictional case vignette to illustrate use of the intervention. This section provides a clinical resource that may be helpful to clinicians interested in actively encouraging rapid behavior change with clients with eating disorders. Highlights: Development and components of the CBT-RR intervention for eating disorder are described. Treatment retention and homework completion rates were good. Alliance with therapist and satisfaction with treatment was high. CBT-RR for eating disorder was feasible to implement and acceptable to participants.